MNEs and industrial structure in host countries: a portfolio analysis of Irish manufacturing - Barry, F; Kearney, C (Journal of International Business Studies, 2006)
Ireland has been very successful in attracting foreign MNEs in high-technology sectors. Although these sectors exhibit faster growth than the traditional low-technology sectors populated primarily by indigenous firms, the high-technology sectors are also more volatile. We use portfolio theory to show that Ireland's FDI strategy has led to a more diversified manufacturing sector that exhibits higher growth without a commensurate increase in volatility and risk.